(untitled) (Research, Society and Development, 2022)
Objective: to understand the impact of relapse of psychoactive substance use from the perspective of women. Matherials and methods: qualitative research carried out with 20 women who use psychoactive substances in treatment at a Psychosocial Care Center in a city in the state of Rio Grande do Sul (Brazil). Individual and open interviews were carried out between February and May 2017, which were the object of thematic analysis. Results: relapse interferes with family and social relationships, weakening affective bonds, causing damage to routine and daily activities due to the effects of substance use and exacerbating negative feelings in women with each relapse, such as guilt, frustration and helplessness. Conclusion: a unique and comprehensive care is needed that addresses the health and social needs derived from the consequences of relapse in women’s lives. Likewise, the need to work on gender issues during care for women is highlighted.